2015
DOI: 10.1016/j.echo.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Coronary Heart Disease with Common Carotid Artery Near and Far Wall Intima-Media Thickness: The Multi-Ethnic Study of Atherosclerosis

Abstract: Background Intima-media thickness (IMT) measured on ultrasound images of the common carotid artery (CCA) is associated with cardiovascular risk factors and events. Based on the physics of ultrasound, CCA far wall IMT measurements are favored over near wall measurements but this theoretical advantage is not well studied. Methods We studied 6606 members of the Multi-Ethnic Study of Atherosclerosis (MESA), a longitudinal cohort study (mean age 62.1 years; 52.7% female) who had near wall and far wall CCA IMT mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Previous studies reporting reference intervals for cIMT confirm the presence of a strong, linear relationship between age and cIMT . The Multi‐Ethnic Study of Atherosclerosis (MESA) also found a strong relationship between age and cIMT . Furthermore, in a previous article we reported that age‐related wall thickening in healthy asymptomatic individuals occurs similarly between the carotid artery as well as peripheral arteries in the upper and lower limb .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies reporting reference intervals for cIMT confirm the presence of a strong, linear relationship between age and cIMT . The Multi‐Ethnic Study of Atherosclerosis (MESA) also found a strong relationship between age and cIMT . Furthermore, in a previous article we reported that age‐related wall thickening in healthy asymptomatic individuals occurs similarly between the carotid artery as well as peripheral arteries in the upper and lower limb .…”
Section: Discussionsupporting
confidence: 58%
“…Each symbol represents a single studied population, with the size of the symbol being related to the sample size (eg, n = <250; n = 250-1000; n = >1000). Abbreviations: cIMT, carotid artery intima-media thickness 24 Furthermore, in a previous article we reported that age-related wall thickening in healthy asymptomatic individuals occurs similarly between the carotid artery as well as peripheral arteries in the upper and lower limb. 10 These data support the idea that the annual increase of cIMT closely follows the chronological aging process.…”
Section: Influence Of CV Disease/risk On the Relation Between Age Amentioning
confidence: 98%
“…Procedurally, participants were properly positioned in a comfortable supine position with their heads rotated 45 degree toward the right, then left in alternative turns for clear visualization of the CIMT of both arteries [ 25 ]. The far wall thickness of both arteries was taken from anterior, lateral, posterior angles by ensuring that these images were visualized from a 10-millimeter distance proximal to the bulk of the common carotid arteries [ 15 , 26 ]. The thickness of layers between medial-adventitial and intimal-luminal interfaces that is marked in double line density was the measurement of the CIMT values.…”
Section: Methodsmentioning
confidence: 99%
“…So far it has been reported that although IMT has a significant relationship with cerebrovascular disease, but not with coronary artery disease. However, concerning the development of coronary artery disease, according to the Multi-Ethnic Study of Atherosclerosis 10) in which IMT was measured in 6,606 subjects (mean age, 62.1years; 52.7% women), the prediction of coronary artery disease onset using IMT of the far side wall of common carotid artery was reported to exceed that using Framingham risk factor (change in C statistic, 0.012; 95% CI, 0.006 -0.017; p < 0.001). In the JART study 11) , measurements of IMT have been standardized using less than 400 patients who had carotid artery wall thickness or atherosclerotic lesions (plaques) (IMT ≥ 1.1 mm) and high LDL-C.…”
Section: Gender Difference Should Be Considered In Practical Dyslipidmentioning
confidence: 99%